2020
DOI: 10.1101/2020.11.16.20232868
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of the Impact of COVID-19 pandemic on population level interest in Skincare: Evidence from a google trends-based Infodemiology study

Abstract: BackgroundCOVID-19 pandemic created an unprecedented disruption of daily life including the pattern of skin related treatments in healthcare settings by issuing stay-at-home orders and newly coronaphobia around the world.ObjectiveThis study aimed to evaluate whether there are any significant changes in population interest for skincare during the COVID-19 pandemic.MethodsFor the skincare, weekly RSV data were extracted for worldwide and 23 counties between August 1, 2016, and August 31, 2020. Interrupted time-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
2
1
0
Order By: Relevance
“…Quarantine‐related lifestyle changes led to different unfavorable conditions such as psychosocial distress, depression, and stress. 2 , 7 COVID‐19 pandemic‐related studies reported higher levels of anxiety similar to the previous investigations in earlier pandemics, such as the outbreak of the severe acute respiratory syndrome‐related to coronavirus in 2003. In an analysis of the Chinese population, 53.8% of individuals reported moderate‐to‐severe psychosocial impact associated with the COVID‐19 pandemic.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Quarantine‐related lifestyle changes led to different unfavorable conditions such as psychosocial distress, depression, and stress. 2 , 7 COVID‐19 pandemic‐related studies reported higher levels of anxiety similar to the previous investigations in earlier pandemics, such as the outbreak of the severe acute respiratory syndrome‐related to coronavirus in 2003. In an analysis of the Chinese population, 53.8% of individuals reported moderate‐to‐severe psychosocial impact associated with the COVID‐19 pandemic.…”
Section: Discussionsupporting
confidence: 83%
“…COVID‐19 pandemic causes a substantial modification in daily social life, and many people worldwide have confronted different difficulties. Quarantine‐related lifestyle changes led to different unfavorable conditions such as psychosocial distress, depression, and stress 2,7 . COVID‐19 pandemic‐related studies reported higher levels of anxiety similar to the previous investigations in earlier pandemics, such as the outbreak of the severe acute respiratory syndrome‐related to coronavirus in 2003.…”
Section: Discussionsupporting
confidence: 75%
“…The high market demand has made skincare products one of the most popular ways to deal with skin concerns [1]. What's more, skincare trends began to rise drastically in 2020, when the COVID-19 pandemic began [2].…”
Section: Introductionmentioning
confidence: 99%